Becoming a research university as a strategic choice in Bahir Dar university፡ A resource dependency perspective - Koye Kassa Getahun; Nigusse Weldemariam Reda; Abeba Seyoum Wube (College of education, Bahir Dar University, 2023)
This paper explored how the need for research universities in Ethiopia is justified, practiced, and could be improved using the strategic tactics of the resource dependency perspective. Bahir Dar University (hereafter referred to as BDU) was taken as a case to understand the need for a research university and its practices. Document analysis was used as a source of data. Consequently, an analysis of various institutional and national secondary sources revealed that the existing uncertainties related to critical resources motivated Bahir Dar University to devise a strategic choice of becoming a research university. The uncertainties are justified in terms of economic, political and institutional conditions. Although the university envisioned becoming a research university by 2025, the existing institutional and national conditions seem to be immature to sustain the necessary resources and conditions that a research university requires. As a result, following the higher education differentiation effort, BDU had to revise its vision and extend the possible time its vision could be realized to 2030. It is concluded that the need for BDU to become a research university seems to be challenging and needs much effort to be realized. Hence, institutional re-arrangements following the strategic tactics of the resource dependency perspective need to be devised to realize the strategic choice of becoming a research university.